1994
DOI: 10.1172/jci117397
|View full text |Cite
|
Sign up to set email alerts
|

Selective response of human airway epithelia to luminal but not serosal solution hypertonicity. Possible role for proximal airway epithelia as an osmolality transducer.

Abstract: The response of cultured human nasal epithelia to hypertonic bathing solutions was tested using ion-selective microelectrode and quantitative microscopy. Raised luminal, but not serosal, osmolality (±150 mM mannitol) decreased Na' absorption but did not induce Cl-secretion. Raised luminal osmolality increased cell Cl-activity, Na' activity, and transepithelial resistance and decreased both apical and basolateral membrane potentials and the fractional resistance of the apical membrane; equivalent circuit analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
65
4

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 26 publications
11
65
4
Order By: Relevance
“…Further studies will be necessary to deter- mine whether luminal mannitol does alter ion transport in vivo, with similar but opposite effects resulting in no significant overall response. However, the responses to luminal saline appear to differ in the two studies with a significant decrease in nasal PD in the current study contrasting with the lack of change in Vt found by WILLUMSEN et al [11]. This may simply reflect the different doses used in the respective studies -the only dose reported in the WILLUMSEN et al study was 75 mM, whilst the smallest dose used in the current study was 150 mM.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Further studies will be necessary to deter- mine whether luminal mannitol does alter ion transport in vivo, with similar but opposite effects resulting in no significant overall response. However, the responses to luminal saline appear to differ in the two studies with a significant decrease in nasal PD in the current study contrasting with the lack of change in Vt found by WILLUMSEN et al [11]. This may simply reflect the different doses used in the respective studies -the only dose reported in the WILLUMSEN et al study was 75 mM, whilst the smallest dose used in the current study was 150 mM.…”
Section: Discussioncontrasting
confidence: 84%
“…Addition of 150 mM mannitol to the luminal surface was associated with decreases (less negative) in both apical (Va) and basolateral (Vb) membrane potentials, with small but variable effects on the transepithelial membrane potential (Vt) in different monolayers. Addition of 75 mM NaCl to the luminal solution also decreased both Va and Vb, but did not alter Vt [11]. The nonsignificant increase in nasal PD found in the current study corresponds with the variable effects on Vt found in the nasal polyp monolayers; Va and Vb cannot be assessed using the nasal PD technique.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Identification of AQP5 expression in bronchial epithelial cells strongly implicates AQP5 as the previously described, but unidentified mercury-sensitive water channel responsible for mediating osmotically driven transcellular water flow and airway surface liquid composition (28,29). It has been shown that a local increase in the osmolarity of the airway surface liquid as a result of respiratory water loss or inhalation of hypertonic saline induces bronchoconstriction in asthmatic patients (30,31).…”
Section: Discussionmentioning
confidence: 93%
“…The RVI can take up to 20 min to be complete [25,26]. There is evidence that the apical membrane of the airway epithelium is more permeable to water than the basolateral membrane [29]. There is also evidence that asthmatic subjects have thickening of the basement membrane [30,31], which could limit the rate of water diffusion when there is a high demand.…”
Section: Discussionmentioning
confidence: 99%